Etnografía escolar del celular como un recurso para la construcción de espacios de fuga. (2018)
This paper socializes the results of an ethnographic research that approach the cellphone use as a lens to analyze the teenager’s socialization dynamics in a private School of Bogotá. To this end, interactions within and outside the classroom were considered, encompassing both regulated and informal spaces. The analysis of these scenarios showed that the use of the mobile phone has a high social attractiveness for adolescents, giving to it a place even in spaces where it is prohibited and inscribing its use in what is called here escape spaces.